A configuração do campo da saúde no sertão do São Francisco (1948-1958) - Rosa, Renata Fernandes do Nascimento (2018)
A historico-social nature study that had as object the health field configuration at the São Francisco´s countryside area. The "São Francisco countryside area", a term used in this work, refers to the region that surrounds the São Francisco river on the border of Bahia’s, Alagoas’, Sergipe’s and Pernambuco’s states.At this point, the waters of the waterfall were dammed with the purpose of power generation by the Hydroelectric Company of the São Francisco - CHESF, in the late 1940s. Therefore a camp was built for the company workers, with a true city infrastructure, which included a small hospital, unique within a field of action about 300 kilometers. Thus, the objectives of this study were: To describe the current social order at the São Francisco countryside area and the Brazilian state´s health policy for this region in between 1948 and 1958; To analyze the configuration of the health field from the SESP public healthcare actions and the hospital actions from CHESF at the São Francisco countryside area; To discuss the symbolic effects of the configuration of the health field at the countryside area of San Francisco. Qualitative study with a social history approach, temporal cut from 1948 to 1958, the implantation of the Nair Alves de Souza Hospital - HNAS had being the initial milestone in the base of the installation of the CHESF camp and the end of the emancipation of the city of Paulo Afonso. The historical sources used were the CHESF company documents, reports, photographs, newspaper clippings. The analysis of the sources was done by the triangulation of the data, in the light of Pierre Bourdieu’s thought, theoretical reference of the study, focusing on the concept of "field" and "state". The research was submitted to the Ethics Committee of the Federal University of Alagoas and was approved by the opinion of number 6056.1416.7.0000.5013. The analysis of the sources allowed the reflection that after the Second War, the SESP preventive model was expanded to the interior of Brazil, and due to the energetic potential of the studied region, it was necessary to clean up and attend to the health of the people who lived there, besides the actions of interiorization of the sanitary model. Thus, a hospital was set up by CHESF, matching the region to the great economic centers, which had as symbolic effects in the health field the consolidation of CHESF hospital actions, developed by the Nair Alves de Souza Hospital, with the extrapolation of actions for people who lived on the fringes of the company's encampment, as well as the citizens of neighboring towns. Another symbolic effect was represented by the partnership between CHESF and SESP for the maintenance of preventive actions for all the population with social and welfare actions and finally the visibility that was given to the work of the nurses who consolidated the current social order.